IoT-Based Atmospheric Parameter and Location Detection System Using LoRa - Ahmad Pazilah, Muhammad Abdul Aziz; Homam, Mariyam Jamilah (Evolution in Electrical and Electronic Engineering, 2022)
ALoRa is a low-power, long-range wireless technology and can be utilized for IoT-based applications. LoRa is suitable to be used in many applications such as smart cities or smart agriculture. In this project, an atmospheric parameters and location tracking system have been developed using LoRa. In addition to the LoRa modules, ESP32, Arduino UNO, GPS module, and DHT11 sensor are also utilized. Location data dan atmospheric parameters data (temperature and humidity) are then sent to the IoT platform (Favoriot). The system is able to transmit data successfully for a distance of 1 km.